On the L1 norm of an exponential sum involving the divisor function - Goldston, D. A.; Pandey, M. (Archiv der Mathematik, 2019)
In this paper, we obtain bounds on the L 1 -norm of the sum ∑ n ≤ x τ ( n ) e ( α n ) where τ ( n ) is the divisor function.